Prolonged release of VEGF and Ang1 from intralesionally implanted hydrogel promotes perilesional vascularization and functional recovery after experimental ischemic stroke. Issue 6 (June 2022) - Yanev, Pavel; van Tilborg, Geralda AF; van der Toorn, Annette; Kong, Xiangmei; Stowe, Ann M; Dijkhuizen, Rick M
Injectable hydrogels can generate and support pro-repair environments in injured tissue. Here we used a slow-releasing drug carrying in situ -forming hydrogel to promote post-stroke recovery in a rat model. Release kinetics were measured in vitro and in vivo with MRI, using gadolinium-labeled albumin (Galbumin), which demonstrated prolonged release over multiple weeks. Subsequently, this hydrogel was used for long-term delivery of vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang1) (Gel VEGF + Ang1, n = 14), in a photothrombotically induced cortical stroke lesion in rats. Control stroke animals were intralesionally injected with saline (Saline, n = 10), non-loaded gel (Gel, n = 10), or a single bolus of VEGF + Ang1 in saline (Saline VEGF + Ang1, n = 10). MRI was executed to guide hydrogel injection. Functional recovery was assessed with sensorimotor function tests, while tissue status and vascularization were monitored by serial in vivo MRI. Significant recovery from sensorimotor deficits from day 28 onwards was only measured in the Gel VEGF + Ang1 group. This was accompanied by significantly increased vascularization in the perilesional cortex. Histology confirmed (re)vascularization and neuronal sparing in perilesional areas. In conclusion, intralesional injection of in situ -forming hydrogel loaded with pro-angiogenic factors can support prolonged brain tissue regeneration and promote functional recovery in the chronic phase post-stroke.